2018
DOI: 10.1111/jne.12649
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neurosteroidogenesis during demyelination and remyelination in cuprizone‐treated mice

Abstract: | INTRODUC TI ONMultiple sclerosis (MS) is a disease of the central nervous system (CNS) leading to the demyelination of white and grey matter, 1 characterised initially in most patients by relapsing-remitting episodes.MS presents loss of oligodendrocytes, axonal injury, neurodegeneration and inflammation. 2,3 A role for steroid hormones has been suggested because the incidence, progression and severity of MS are affected in a sex-dependent manner. 4 Furthermore, the prospective European Pregnancy in Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The animals were divided into four experimental groups depending on feed type (N = 6/group); a control pellet group, a cuprizone pellet group, a control powder group, and a cuprizone powder group. 6 mice/group was chosen as power calculation (using G*Power Version 3.1 59 ) at α-level of 0.05 showed that it was sufficient for an 80% chance of detecting the published effect size of 2.02 for immunohistochemical measures of myelin and glia in the corpus callosum following cuprizone treatment 60 . Animals were housed two animals per cage and were weighed daily, and if cuprizone-fed animals weighed less than 85% of their body weight at the start of the experimental period, they were weighed twice daily and their feed was supplemented with normal powdered chow until they returned to above the 85% threshold.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were divided into four experimental groups depending on feed type (N = 6/group); a control pellet group, a cuprizone pellet group, a control powder group, and a cuprizone powder group. 6 mice/group was chosen as power calculation (using G*Power Version 3.1 59 ) at α-level of 0.05 showed that it was sufficient for an 80% chance of detecting the published effect size of 2.02 for immunohistochemical measures of myelin and glia in the corpus callosum following cuprizone treatment 60 . Animals were housed two animals per cage and were weighed daily, and if cuprizone-fed animals weighed less than 85% of their body weight at the start of the experimental period, they were weighed twice daily and their feed was supplemented with normal powdered chow until they returned to above the 85% threshold.…”
Section: Methodsmentioning
confidence: 99%
“…The hippocampus and cerebral cortex show decreased expression levels of StAR, P450scc and 5α-R in a demyelination mouse model induced by the injection of cuprizone (Leicaj et al, 2018). Neuroactive steroid levels are also altered in an experimental model of amyotrophic lateral sclerosis.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…In a recent study, Leicaj et al evaluated the expression of different enzymes of steroidogenesis in the brain of mice subjected to demyelination by cuprizone, a model of multiple sclerosis. They showed that the expression of P450scc and 5α-reductase was decreased in the hippocampus, cortex, and corpus callosum during the demyelination period and was restored to control levels during remyelination [60]. Using another model of multiple sclerosis, Noorbakhsh et al have reported a significant decrease in 3α-HSD expression in the brain of autoimmune encephalomyelitis (EAE) mice [61].…”
Section: Introductionmentioning
confidence: 99%